Pc1 hydromagnetic emissions of chevron type - Alexandrovich, Parkhomov Vladimir; Battuulai, Tsegmed; Victorovich, Dovbnya Boris; Yurievich, Khomutov Sergey; Grigorieivich, Eselevich Victor; Yurievich, Glinskyi Igor (Proceedings of the Mongolian Academy of Sciences, 2023)
The article presents the results of studying novel bursts of ULF emissions within 0.5–2.5 Hz (Pc1 geomagnetic pulsations) with a simultaneous increase ( 0.01 Hz/min) and decrease in frequency ( 0.01 Hz/min) lagging by 5÷10 min from the initial mean frequency ( 0.6 Hz). From their formal resemblance with the stripes on military officer uniforms, these emissions are called Pc1 chevrons. The bursts were observed during strong short-term geomagnetic disturbances ( 1 hour): substorms with high gradient of ionospheric currents+ intensification (dD/dt or dH/dt 1–1.3 nT/s). We present the main parameters and couplings of these emissions with substorm geophysical phenomena of 11.02.1985, 06.04.1997 and 18.07.2013 events. Polar satellite observations of auroras are compared with LANL-91, 94 and THEMIS-A observations of charged particle fluxes. Possible mechanisms generating oscillations are also discussed.